2016
DOI: 10.1590/1414-431x20154888
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotubes functionalized with sodium hyaluronate enhance bone mineralization

Abstract: The aim of this study was to evaluate the effects of sodium hyaluronate (HY), single-walled carbon nanotubes (SWCNTs) and HY-functionalized SWCNTs (HY-SWCNTs) on the behavior of primary osteoblasts, as well as to investigate the deposition of inorganic crystals on titanium surfaces coated with these biocomposites. Primary osteoblasts were obtained from the calvarial bones of male newborn Wistar rats (5 rats for each cell extraction). We assessed cell viability using the 3-(4,5-dimethylthiazol-2-yl)-2,5-dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Here, it was observed that HY, MWCNTs, and HY-MWCNTs increased the expression of BMP-2, thereby suggesting an acceleration of tibia bone repair. Our data corroborate the results found by Sá et al [2016]. Both studies reported a pronounced increase in BMP-2 expression induced by CNTs alone, evidencing an important role of this material in the mineralization process.…”
Section: Discussionsupporting
confidence: 92%
“…Here, it was observed that HY, MWCNTs, and HY-MWCNTs increased the expression of BMP-2, thereby suggesting an acceleration of tibia bone repair. Our data corroborate the results found by Sá et al [2016]. Both studies reported a pronounced increase in BMP-2 expression induced by CNTs alone, evidencing an important role of this material in the mineralization process.…”
Section: Discussionsupporting
confidence: 92%
“…This observation contradicts the predominant trend on CNT effects on collagen production described in the literature since multiple studies have found that CNT positively impacts collagen production. (39,40) Considering this observation, further analysis will be necessary to comprehend this result better.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 98%
“…After the incubation, isopropanol/0.04 N HCl was added to MTTtreated cells, and the cells were agitated to promote elution of formazan. Then, the supernatants were quantified by measuring the absorbance at 550 nm in a SpectraMax M5 e microplate reader (Molecular Devices, Minneapolis, MN, USA) [6].…”
Section: Mtt Reduction Assaymentioning
confidence: 99%
“…The stained cells were observed on an inverted microscope and photographed to capture the area of mineralization, which was indicated by black staining. Ten images per culture dish well were randomly acquired, and then the mineralized area was quantified by using Image J software [6].…”
Section: Determination Of Ca 2+ Accumulation By Von Kossa Stainingmentioning
confidence: 99%